2011
DOI: 10.1128/jcm.05212-11
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Xpert MTB/RIF RUO Assay and IS 6110 Real-Time PCR for Mycobacterium tuberculosis Detection in Clinical Samples

Abstract: The Cepheid Xpert MTB/RIF research-use-only (RUO) assay and a laboratory-developed test (LDT) targeting IS6110 were evaluated and compared to mycobacterial culture as the gold standard. The performance characteristics of both molecular assays were determined by using 112 specimens from 90 patients, including 89 pulmonary specimens and 23 extrapulmonary specimens. Of the specimens tested, 37 (33%) were culture positive for the Mycobacterium tuberculosis complex; 29 were pulmonary, and 8 were extrapulmonary. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 15 publications
5
36
0
5
Order By: Relevance
“…Performance was in line with generally accepted characteristics of molecular testing for M. tuberculosis: 90-100% sensitivity in microscopy smear-positive sputum specimens and 55-75% among smearnegative cases (Armand et al, 2011, Dinnes et al, 2007, Miller et al, 2011, Steingart et al, 2014. There was no apparent effect of chemical composition of PS-MTM on detection of lower bacillary loads as diagnostic performance among smear-negative cases was adequate.We did not test amplification suppression, but think that the effect, if present, was minimal as we were able to successfully amplify M. tuberculosis at relatively low CFU/ml as well as detect smear negative TB cases in the clinical laboratory evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…Performance was in line with generally accepted characteristics of molecular testing for M. tuberculosis: 90-100% sensitivity in microscopy smear-positive sputum specimens and 55-75% among smearnegative cases (Armand et al, 2011, Dinnes et al, 2007, Miller et al, 2011, Steingart et al, 2014. There was no apparent effect of chemical composition of PS-MTM on detection of lower bacillary loads as diagnostic performance among smear-negative cases was adequate.We did not test amplification suppression, but think that the effect, if present, was minimal as we were able to successfully amplify M. tuberculosis at relatively low CFU/ml as well as detect smear negative TB cases in the clinical laboratory evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…In one previous study, Armand et al (2011) demonstrated the results from just 32 nonrespiratory samples and found an overall sensitivity of 53% that was substantially lower than that obtained using an in-house IS6110-based real-time PCR assay (78%) [27]. By contrast, the sensitivity of the Xpert assay was 75% while the IS6110 real time assay's sensitivitiy was 0% in smear negative extrapulmonary specimens [28].…”
Section: Comparative Study With Other Assaysmentioning
confidence: 99%
“…The Xpert assay provides excellent sensitivity and specificity from direct specimens while providing a same day turn-around time for results (Helb et al, 2010;Boehme et al, 2011;Marlowe et al, 2011;Rachow et al, 2011;Scott et al, 2011). In addition, the assay provides immediate information on RIF resistance and has recently been successfully evaluated using non-respiratory specimens (Ioannidis et al, 2011;Miller et al, 2011).…”
Section: Future Directionsmentioning
confidence: 99%